2558. Predicting β-Lactam Resistance Using Whole Genome Sequencing (WGS) in Klebsiella pneumoniae: The Challenge of β-Lactam Inhibitors. (26th November 2018) - Hujer, Andrea; Long, Wesley; Olsen, Randall; Kreiswirth, Barry N; Evans, Scott R; Musser, James; Bonomo, Robert
Abstract: Background: Antimicrobial susceptibility testing (AST) is the major driver in designing effective therapy. As multiple resistance determinants can demonstrate the same phenotype (e.g., inhibitor resistant [IR], extended spectrum [ES], and carbapenem hydrolyzing [CH] β-lactamases), critical information provided from AST for therapy, stewardship, and infection control is currently lacking. WGS provides more comprehensive genetic data, explaining phenotype, and provides insight into clonality. Efforts are in development that apply novel statistical methods (e.g., PRIMERS I-IV) and machine learning ( Sci Reports, 2108, 8, 421) to interpret results accurately and anticipate AST. Using a collection of clinical strains that spanned a 3.5-year period, we tested how well the detection of problematic IR, ES, and CH bla resistance genes predicted phenotype. Methods: Fourty-one isolates were chosen for AST from a collection of 1, 777 WGS K. pneumoniae . Isolates chosen possessed the following β-lactamases: (9 isolates) NDM; (3) NDM and OXA-48; (5) KPC-8 or KPC-14; (24) with a very complex β-lactamase background (all possessed an inhibitor resistant TEM (IRT), SHV ESBL, +/− CTX-M, and/or +/− KPC). AST was performed using CLSI methods for piperacillin/tazobactam (PIP/TAZO), ceftazidime (CAZ), aztreonam (ATM), ceftazidime/avibactam (CAZ/AVI), CAZ/AVI/ATM, and ceftolozane/tazobactam (TOL/TAZO) by disk diffusion assay. Results: Presented below. Conclusion: In all cases, bla NDM-1 and bla NDM-1/OXA-48 containing isolates were resistant to CAZ/AVI; the addition of ATM fully restored susceptibility to CAZ/AVI. Surprisingly, clinical K. pneumoniae isolates bearing KPC-8 (V240G) and KPC-14 did not test fully resistant to CAZ/AVI, suggesting a more complex mechanism than the D179Y variant of KPC-3. Lastly, despite the complexity of the β-lactamase background, CAZ/AVI retained potency. Interestingly, TOL/TAZO maintained efficacy in these same complex backgrounds in the absence of NDM, KPC, and SHV-12. As previously shown in PRIMERS I-II, PIP/TAZO resistance was not observed in the majority of isolates as was predicted by the genotype. WGS in K. pneumoniae to predict AST results and potentially guide clinical decisions is improved for novel combinations like CAZ/AVI. Disclosures: All authors: No reported disclosures.